Narrative of the Arctic land expedition to the mouth of the Great Fish River : and along the shores of the Arctic Ocean in the years 1833, 1834, and 1835 - Back, George, Sir, 1796-1878. (Philadelphia : E.L. Carey & A. Hart, 1837)
Mode of access: Internet.